OPTIMALISASI TENAGA KERJA PADA PT DC DI BIDANG PRODUCTION AND REPAIRMENT DENGAN MENGGUNAKAN METODE FULL TIME EQUIVALENT (FTE) - Farhan Ihsan Putra (2020)
PT.DC is a manufacturing company that manufactures and repairs pumps.One main problem in PT.DC is the delay in repairs to the LP Drain Pump product due to suboptimal performance of the workforce which causes the product to be assembled but still lacking balance so there is a delay in the delivery of the LP Drain Pump product. In this research, the method used is Full Time Equivalent (FTE). Workload received by each machine operator and the number of workers by the workload carried out in the field of production and repairment are for cutting work stations by 1.09 and 5 people, welding by 0.63 and 3 people, painting by 0.74 and 2 people, straighten of 0.36 and 1 person, lathe of 0.54 and 3 people, HBM of 0.6 and 3 people, milling of 0.59 and 2 people, balancing of 0.45 and 1 person, assembly of 0.42 and 2 people, hydrotest of 0.50 and 2 people, packaging of 0.53 and 2 people. The majority of work stations have underloaded workloads, caused by workers who do not utilize their time properly, for example over time. For this reason, companies need to tighten workers' control in the field of production and repairment so that there is no delay.